The changing paradigm of ethics in uterus transplantation: a systematic review. (6th January 2020) - Ngaage, Ledibabari M.; Ike, Samantha; Elegbede, Adekunle; Vercler, Christian J.; Gebran, Selim; Liang, Fan; Rada, Erin M.; Cooney, Carisa; Brandacher, Gerald; Redett, Richard J.; Johannesson, Liza; Rasko, Yvonne M.
Summary: The first uterus transplantation was performed in 2000. As key milestones are reached (long‐lasting graft survival in 2011, and first birth from a transplanted womb in 2014), the ethical debate around uterus transplant evolves. We performed a systematic review of articles on uterus transplantation. Ethical themes were extracted and categorized according to four bioethical principles. Papers were divided into time periods separated by key events in uterus transplant history: Phase I (first technical achievement, 2002–2011), Phase II (clinical achievement, 2012–2014), and Phase III (after the first childbirth, 2015–2018). Eighty‐one articles were included. The majority of ethics papers were published in Phase III (65%, P  < 0.0001), that is after the first birth. Eighty percent of papers discussed nonmaleficence making it the most discussed principle. The first birth acted as a pivotal point: nonmaleficence was discussed by a lower proportion of articles ( P  = 0.0073), as was beneficence ( P  = 0.0309). However, discussion of justice increased to become the most discussed principle of the time period ( P  = 0.0085). The ethical debate surrounding uterus transplantation has evolved around landmark events that signify scientific progress. As safety and efficacy become evident, the focus of ethical debate shifts from clinical equipoise to socioeconomic challenges and equitable access to uterus transplantation.